2019
DOI: 10.1088/1742-6596/1217/1/012175
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of medicinal plants in Penggaron tourism forest of Central Java, Indonesia

Abstract: Nowadays, the need for medicinal plants as raw materials of traditional medicine is increasing. This study aims to determine the plant species that potential as medicine and its abundance in Penggaron Tourism Forest. Study sites were in the mixed forests and pine forests of Penggaron tourism forest. Vegetation sampling was carried out using a plot method with a size of 10 x 10 m for tree strata, 5 x 5 m for shrub strata and 1 x 1 m for grass or herbaceous strata. Each species of medicinal plant found was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…One species of Asteraceae, Chromolaena odorata was the most abundant. This species is common medicinal plants in Thailand and widely distributed in the tropics region [14] Table 2 shows the abundance of medicinal plants from the each section. The most abundant species in the sites were D. esculentum and followed by C. hirta, C. odorata, S. mahagoni, E. valerianifolius, E. elatior, Coffea sp., C. asiatica, A. moluccana, and B. multiplex.…”
Section: Species Richness and Abundance Of Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…One species of Asteraceae, Chromolaena odorata was the most abundant. This species is common medicinal plants in Thailand and widely distributed in the tropics region [14] Table 2 shows the abundance of medicinal plants from the each section. The most abundant species in the sites were D. esculentum and followed by C. hirta, C. odorata, S. mahagoni, E. valerianifolius, E. elatior, Coffea sp., C. asiatica, A. moluccana, and B. multiplex.…”
Section: Species Richness and Abundance Of Medicinal Plantsmentioning
confidence: 99%
“…However, this species has lots of health benefits and is commonly used by people in ethnopharmacological uses such as treatment fotr stomachache, coughs, and colds, toothache, malaria, Advances in Biological Sciences Research, volume 13 diarrhea, skin infection [23]. Utami and Rahadian [14] reported that this species was one of the most prevalent medicinal plants found in Penggaron tourism forest of Central Java, Indonesia that benefit as anti-inflames and anti-diabetic. Rohman et al [24] reported that the Tengger tribe located in Bromo Tengger Semeru National Park, East Java utilized C. odorata as an insect repellent.…”
Section: Species Richness and Abundance Of Medicinal Plantsmentioning
confidence: 99%
“…[8] [27] Several studies mention the benefits of this plant, among others to treat insomnia, rheumatism, asthma, ulcers, nourish the heart, reduce inflammation. [9] [22] Healing wounds, even overcoming the symptoms of diabetes. [10] Various pharmacological activities of C. ternatea were reported in Vol 01 2022, pp 8-17 e-ISSN: XXXX-XXXX DOI: https://doi.org/10.54482/ELECTROLYTE/ DOI: https://doi.org/10.54482/ ELECTROLYTE/ literature such as antimicrobial, antipyretic, anti-inflammatory, analgesic, diuretic, local anaesthetic, antidiabetic, insecticidal, blood platelet aggregation inhibiting and vascular smooth muscle relaxant properties.…”
Section: Introductionmentioning
confidence: 99%